Comparative Studies on Isolation and Characterization of Allinase from Garlic and Onion using PEGylation-A Novel Method - Rathnasamy, Senthilkumar; Rufus Auxilia, L. (Asian Journal of Chemistry, 2014)
Allium plants including garlic (Allium sativum) and onion (Allium cepa) contain an enzyme allinase (E.C-4.4.1.4), which is an enzyme responsible for the production of thio sulphates, a promising therapeutically potential compound. PEG (polyethylene glycol) is used in this study for the first time, to precipitate a protein. Four fold purification was done for both garlic and onion. The protein yield of the garlic was greater than onion shoots. 6.2 mg protein was the yield at the step in garlic, whereas it was 0.6 mg in onion shoots. The total protein content in the garlic is 6.1 g in the 100 g of garlic where as it is 1.6 g in the onion shoots.